Mental health consequences of sexual assault among first-year college women. Issue 6 (18th August 2018) - Carey, Kate B.; Norris, Alyssa L.; Durney, Sarah E.; Shepardson, Robyn L.; Carey, Michael P.
ABSTRACT: Objective : One in five college women experience unwanted sexual contact while in college, with first-year women being at the greatest risk. Given these data, we investigate how first-semester sexual assault impacts college women's mental health.Participants : 483 female first-year students enrolled in the study during the first month of college.Methods : All participants completed a health questionnaire when they arrived on campus and again at the end of their first semester.Results : Twelve percent of participants reported sexual assault during the first semester of college. After controlling for baseline mental health and precollege sexual assault history, sexual assault during the first semester predicted clinically significant levels of anxiety and depression at the end of that semester.Conclusions : The occurrence of sexual assault early in college has adverse mental health consequences.